2014
DOI: 10.14202/vetworld.2014.194-199
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of economic losses due to Peste de Petits Ruminants in small ruminants in India

Abstract: Aim: To develop a simple mathematical model to assess the losses due to peste des petits ruminants (PPR) in small ruminants in India. Materials and Methods:The study was based on cases and deaths in goats and sheep due to PPR from the average combined data on ovine/caprine as published by Government of India for the last 5 years (2008)(2009)(2010)(2011)(2012). All possible direct and indirect losses due to the disease, viz. mortality losses, losses due to direct reduction in milk/wool yield, losses due to repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…PPR affects small ruminants and it is not a zoonosis. Goats have been reported to be more susceptible than sheep , but this has not been confirmed in other outbreaks (Singh et al, 2014…”
Section: Resistance Of the Virusmentioning
confidence: 93%
“…PPR affects small ruminants and it is not a zoonosis. Goats have been reported to be more susceptible than sheep , but this has not been confirmed in other outbreaks (Singh et al, 2014…”
Section: Resistance Of the Virusmentioning
confidence: 93%
“…This was worked out as the product of the number of animals that died due to PPR (D A : more than 12 months of age; D Y : between 6 to 12 months; and D K/L : below 6 months of age), and the probable market value (P A , P Y , and P K/L , respectively) of the animal. Mortality losses were categorised by age group because earlier studies have reported significant differences in deaths according to age (5,6).…”
Section: Loss From Mortalitymentioning
confidence: 99%
“…Singh et al (6) estimated the economic losses due to PPR in India at US $0.25 million/year, using official data on the incidence and number of deaths. This estimate would appear to be too low and reflects the under-reporting of animal disease.…”
Section: Introductionmentioning
confidence: 99%
“…The disease was first reported in 1987 from Arasur village, Tamil Nadu state and later spread to other states and the country became endemic for the disease (Singh et al., ). In India, annual loss reported in the literature was INR 88,951 million (Singh, Bardhan, Verma, Prasad, & Sinha, ), INR 16,116 million (Govindaraj, Balamurugan, & Rahman, ) and INR 45,710–46,830 million (USD 653–669 million; Bardhan et al., ). Considering the importance of the disease, a live‐attenuated PPR vaccine that provides immunity for 3–6 years was developed by ICAR‐Indian Veterinary Research Institute (Sreenivasa, Dhar, Singh, & Bandyopadhyay, ).…”
Section: Introductionmentioning
confidence: 99%